Enhancing Photocatalytic Activity of NO Removal through an In Situ Control of Oxygen Vacancies in Growth of TiO2. Issue 19 (7th August 2019) - Shen, Xiaoling; Dong, Guohui; Wang, Lan; Ye, Liqun; Sun, Jianwu
Abstract: Although defects play an important role in the photocatalytic activity of TiO2, the mechanism of the photocatalytic activity related to different defects remains disputable. Moreover, the reported methods to introduce defects raise the preparation cost. In this work, different types of defects including O‐vacancy cluster, surface O‐vacancy, and bulk O‐vacancy defects are in situ introduced in TiO2 by controlling the crystallization temperature. The medium‐degree crystallinity TiO2 sample mainly containing surface O‐vacancies exhibits the best NO removal activity. The systematic study of photocatalytic mechanism demonstrates that the surface O‐vacancies significantly promote the adsorption of H2 O molecules and improve charge transfer to the adsorbed H2 O forming ·OH, thus dramatically enhancing the photocatalytic NO removal activity. On the contrary, bulk O‐vacancies neither help the adsorption of H2 O molecules, nor improve the charge transfer to H2 O. Abstract : The medium‐degree crystallinity TiO2 sample mainly containing surface O‐vacancies (in situ introduced) exhibits the excellent NO removal activity. The systematic study of photocatalytic mechanism demonstrates that the surface O‐vacancies significantly promote the adsorption of H2 O molecules and improve charge transfer to the adsorbed H2 O forming ·OH, thus dramatically enhancing the photocatalytic NO removal activity.